Sorption of zinc using microwave incinerated sugarcane bagasse ash (MISCBA) and raw bagasse - Salihi, I.U. (Penerbit UTM Press, 2016)
Release of contaminated wastewater containing toxic pollutants has adverse negative effects to the receiving water environment. Heavy metals are non-biodegradable, with longer half âlife and overtime, and can accumulate in living organism. Therefore, it is important to remove heavy metals from wastewater for its safe disposal. In this study, activated carbon prepared from thermal incineration of sugarcane bagasse was used in removing zinc from synthetic solution. The prepared carbon is termed as microwave incinerated sugarcane bagasse ash (MISCBA). Raw non-incinerated bagasse was also employed to compare the removal capacities of the two adsorbents (MISCBA and raw bagasse). Parameters including pH, contact time, initial metal concentrations and adsorbents dosages were examined. The results showed that pH of 6.0, contact time 3 hours and adsorbents dosage of 12 g/L were found to be optimum for zinc removal. Removal capacities of 21.05 mg/g and 13.4 mg/g were determined for MISCBA and raw bagasse, respectively. Freundlich correlation coefficients for MISCBA and raw bagasse were found to be 0.7508 and 0.9233, respectively. Langmuir correlation coefficients were 0.9231 and 0.6423, for MISCBA and bagasse respectively. Â© 2016 Penerbit UTM Press. All rights reserved.